Cigarette smoke modifies neutrophil chemotaxis, neutrophil extracellular trap formation and inflammatory response‐related gene expression. (25th March 2018) - White, P. C.; Hirschfeld, J.; Milward, M. R.; Cooper, P. R.; Wright, H. J.; Matthews, J. B.; Chapple, I. L.C.
Abstract : Background and Objective: Cigarette smoking is a major risk factor for periodontitis, and smoking perturbs neutrophil reactive oxygen species production. This study tested the hypothesis that cigarette smoke extract (CSE) and its components/metabolites nicotine, cotinine and thiocyanate (SCN‐), may influence neutrophil functions. Material and Methods: Chemotaxis was assessed in neutrophils pre‐treated with CSE using real‐time video microscopy. Neutrophil extracellular trap (NET) release in response to CSE, nicotine, cotinine, SCN‐ as well as to phorbol 12‐myristate‐13‐acetate and hypochlorous acid following pre‐treatment with CSE, nicotine, cotinine or SCN‐ was assessed using fluorescence‐based assays. The impact of CSE and SCN‐ treatment on neutrophil respiratory burst‐ and inflammation‐related gene expression (NFKBIE, DNAJB1, CXCL8, NCF1, NCF2, CYBB) was determined by real‐time polymerase chain reaction. Results: Both CSE and SCN‐ pre‐treatment inhibited phorbol 12‐myristate‐13‐acetate‐stimulated NET release. Additionally, SCN‐ inhibited hypochlorous acid‐stimulated NET formation, while SCN‐ alone stimulated NET release. Overall, neutrophils pre‐treated with CSE exhibited reduced speed, velocity and directionality relative to untreated neutrophils. Although CSE and SCN‐ promoted DNAJB1 expression, increased redox‐related gene expression was only detected in response to SCN‐. Conclusion: These results suggest that CSE can alter ex vivo neutrophil activation by mechanisms independent of SCN‐ and nicotine, and SCN‐ may contribute to the perturbed innate immune responses observed in smokers.